2016
DOI: 10.1049/htl.2015.0037
|View full text |Cite
|
Sign up to set email alerts
|

Non‐invasive, home‐based electroencephalography hypoglycaemia warning system for personal monitoring using skin surface electrodes: a single‐case feasibility study

Abstract: The feasibility of a non-invasive EEG-based hypoglycaemia warning system for personal monitoring in the home has been demonstrated in a single case study. The results suggest that further studies are warranted to evaluate the system prospectively in a larger group of participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The data was recorded using a smartphone-based EEG system (Clewett et al 2016 ; Bateson 2018 ; Bateson and Asghar 2021 ), with a sampling rate of 250 Hz, and was affixed to the backrest of a chair upon which the participant was sitting. EEG signals were acquired from 19 Ag/AgCl scalp electrodes (Fp1, Fp2, F7, F3, Fz, F4, F8, T3, C3, Cz, C4, T4, T5, P3, Pz, P4, T6, O1, O2) configured in the international 10–20 arrangement using an EEG headcap (Sleepcap, electrodes encased in a soft sponge material, cables located internally, Spes Medica).…”
Section: Methodsmentioning
confidence: 99%
“…The data was recorded using a smartphone-based EEG system (Clewett et al 2016 ; Bateson 2018 ; Bateson and Asghar 2021 ), with a sampling rate of 250 Hz, and was affixed to the backrest of a chair upon which the participant was sitting. EEG signals were acquired from 19 Ag/AgCl scalp electrodes (Fp1, Fp2, F7, F3, Fz, F4, F8, T3, C3, Cz, C4, T4, T5, P3, Pz, P4, T6, O1, O2) configured in the international 10–20 arrangement using an EEG headcap (Sleepcap, electrodes encased in a soft sponge material, cables located internally, Spes Medica).…”
Section: Methodsmentioning
confidence: 99%
“…Schechter et al (Schechter et al, 2012) used a sensor system of HR, perspiration (unprocessed skin conductance at the fingertips), skin temperature and tremor (by accelerometer) measurements and obtained a sensitivity of 100% and a specificity of 85.7% in detecting nocturnal hypoglycemia in a pilot study in ten adolescents with type 1 diabetes. Clewett et al demonstrated feasibility of noninvasive EEG-based hypoglycemia warning in a single case study (Clewett et al, 2016).…”
Section: Comparison To Other Workmentioning
confidence: 99%